Економіка знань та заходи задоволення потреб споживачів у послугах вищої освіти - Букало, Надія Артемівна; Bukalo, Nadiia A. (Національний університет "Львівська політехніка", 2012)
Досліджено сутність категорії “економіка знань”, розглянуто одну із сфер економіки знань – освіту, запропоновано заходи щодо задоволення потреб споживачів у освітніх послугах вищих навчальних закладів. The article examines the essence of the category of “knowledge economy”, considered one of the areas of the knowledge economy - education, the proposed measures to meet the needs of consumers in the educational services of higher education.
Knowledge economy and measures customer satisfaction with services of higher education
Keywords: Освітні послуги; економіка знань; потреби; вища освіта; educational services; knowledge economy; the needs of higher education